Mothership - Leicht, Martin; Neal, Isla (Leicht, Martin. Ever-expanding universe, 2016)
"If Elvie Nara could do it over again, she probably would not have enrolled at the Hanover School for Expecting Teen Mothers for her junior year of high school. Orbiting Earth in a decommissioned space cruiser loses some of its charm when there's a baby practicing karate on your bladder. Then again, she probably wouldn't have gotten involved with sweet-but-dumb Cole Archer in the first place, since he's the moron who got her pregnant and then bailed. The only thing that could possibly make Elvie's year any worse would be if, say, the ship were attacked by ray gun-toting commandos, and the school's faculty turned out to be totally evil. Oh, and if Cole Archer were one of the commandos. Yeah, that'd be worse." -- Page [4] cover.